Śladami „złotej kohorty” (Dmitrij Bykow, „Uniewinnienie”) - Zywert, Aleksandra (Studia Rossica Posnaniensia, 2016)
Dmitry Bykov’s novel Justification, created within the convention of alternative history, is a story about a fruitless attempt to justify Stalin’s crimes. The work combines mythologizing and demythologizing tendencies, which makes it an interesting example of quasi-historical prose. Moreover, the novel constitutes a significant voice in the debate on Russia's present condition and prospects.